Assessment of Students' Self-Efficacy in Learning Scientific Kitâbah Based on Artificial Intelligence Website - Ali Subhan; Raodah; Lailatul Qomariyah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
Learning the scientific kitabah is a challenge for students because needing the writing guidelines. Lecturer a crucial role in improving students' self-efficacy, both in performance and affective aspects. Lecturer can do it with learning using an artificial intelligence website based. This is a useful learning technology and provides time efficiency in learning. The purpose of this study is to assess students' self-efficacy in achieving learning outcomes in scientific literature based on a website application that can reduce excessive anxiety and worry about inability students in learning scientific scriptures. This research method uses a descriptive qualitative quantitative approach in a one-group pretest-posttest design. Instrument research using self-efficacy ability test based on 4 factors and 14 inductions of self-efficacy validated with a likert scale, and then interview guidelines. The result founded self-efficacy average post score test higher compared to with a pre-test score of 4.1>3.4. The correlation between both of 0.272 with a significance of 0.168. The calculated t value is -6.629 with P Value (significance) of 0.000. By setting a significance level of 5%, it shows that the calculated is t value > t table, namely -6.629 > -2.479 with Ha accepted.